A review of the Neotropical microcaddisfly genus Acostatrichia Mosely, 1939 with description of a new species from Brazil (Trichoptera: Hydroptilidae: Leucotrichiinae) - Santos, Allan Paulo Moreira (Zootaxa, 2020)
The microcaddisfly genus Acostatrichia Mosely (Leucotrichiinae, Leucotrichiini) is revised. Based on morphological features of the adult male, species assigned to the genus are here divided into three species groups: A. plaumanni Group, A. brevipenis Group, and A. cerna Group. After examination of type specimens, the subjective synonymy of Acostatrichia darda Oláh & Flint, A. hosulaba Oláh & Flint, and A. pika Oláh & Flint is proposed, with the first name being chosen to have priority over the other two. Acostatrichia ketvilla Oláh & Flint is considered a junior synonym of Costatrichia nelsonferreirai Santos & Nessimian, and another 3 species are removed from Acostatrichia: A. tapada Oláh & Flint and A. rovidka Oláh & Flint are transferred to Costatrichia; and A. topora Oláh & Flint is transferred to Leucotrichia Mosely. A new species, Acostatrichia araca sp. nov. is described and illustrated from northern Brazil; descriptions and illustrations are also provided for the other 11 Acostatrichia species. After these nomenclatural acts, the genus Acostatrichia includes 15 species restricted to South America.